2014
DOI: 10.1111/eip.12141
|View full text |Cite
|
Sign up to set email alerts
|

Combining depot antipsychotic with an assertive monitoring programme for treating first‐episode schizophrenia in a resource‐constrained setting

Abstract: Combination of depot antipsychotic with an AMP may be an effective and safe intervention in early phases of schizophrenia, and may be particularly suitable for resource-constrained settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…This is an important finding as a recent study conducted in the Western Cape has shown that low dose depot FGA together with assertive monitoring programmes may be a safe and effective intervention for patients with first episode psychosis. 17 Further studies at this hospital could aim to examine the use of antipsychotic drugs in the first episode of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding as a recent study conducted in the Western Cape has shown that low dose depot FGA together with assertive monitoring programmes may be a safe and effective intervention for patients with first episode psychosis. 17 Further studies at this hospital could aim to examine the use of antipsychotic drugs in the first episode of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome is symptom severity as assessed with the PANSS score. Based on our previous naturalistic follow-up study of patients with psychosis undergoing treatment [ 37 ], we estimate that a mean difference of 7.5 units on the total PANSS outcome scores between the two arms will represent a clinically significant difference (given that a standard deviation of 20 was obtained for the PANSS in that study). With the target effect size of 0.38, an uninflated sample size of 112 patients per arm will be required to provide a power of 80% and at an alpha of 0.05.…”
Section: Method/designmentioning
confidence: 99%
“…The authors identified an increased content of specific genomic insertions in synaptic genes in affected subjects and three of these elements are placed in the intronic region of GRM3 , GRM5 and GRM7 . Beside case-control experimental studies, NGS methods have been applied in SCZ also to analyze drug treatment response, identifying no connection between GRMs and antipsychotic effect [ 74 ].…”
Section: Insights From Next Generation Sequencing Studiesmentioning
confidence: 99%